ANALYSIS OF COUNTRY RISK IN PERU - Ordinola Valdez, Andrea Carmen Lidia (2024)
The research presents the evolution of country risk and Gross Domestic Product in Peru in the period 2007-2021, taking into account 180 observations; with the purpose of focusing the study on two years coinciding with the pandemic; in addition to carrying out an analysis of country risk in the Latin American ranking. The research is pure, with a quantitative descriptive, transversal approach, based on the statistical and econometric analysis of the data extracted from the Central Reserve Bank of Peru and the National Institute of Statistics and Informatics, evaluating the assumption of non-autocorrelation, non-multicollinearity and homoscedasticity.